Characteristics and outcomes in patients with infective endocarditis caused by Enterococcus faecium and Enterococcus faecalis. (3rd October 2022) - Try Lenz, I; Pries-Heje, M; Hjulmand, J; Hasselbalch, R B; Jarloev, J O; Faurholt-Jepsen, D; Moser, C; Iversen, K; Bundgaard, H
Abstract: Background: Enterococcus faecalis is the third most common cause of infective endocarditis (IE) and has been associated with a higher risk of relapse and death. Within the enterococcus species, E. faecium is the second most frequent cause of IE. As IE from E. faecalis or E. faecium most likely have different presentations and outcomes, research is needed for individualised and optimised clinical management. Purpose: This study aims to characterise baseline characteristics and clinical outcomes for patients with IE caused by E. faecalis or E. faecium, including short- and long-term mortality and relapse. Additionally, we aim to determine risk factors associated with IE caused by the two bacterial species. Methods: This is a retrospective study of patients hospitalised with at least one positive blood culture with E. faecalis or E. faecium between January 1, 2016 and December 31, 2018 at two large hospitals in Denmark. IE was diagnosed according to the modified Duke criteria. Index and follow-up data were collected from medical records. Categorical values were compared using chi-square test and categorial data using students t-test. Results: 614 patients had a positive blood culture with either E. faecalis (n=279) or E. faecium (n=335). Of these, 64 (10.4%) patients developed IE; E. faecalis in 56 patients (87.5%, male 83.3%, mean age 70 years (SD 14)) and E. faecium in 8 patients (12.5%, male 75.0%, mean age 65 years (SD 13)). The prevalence of IE was 20.1% for E. faecalis bacteraemia and 2.4% for E. faecium bacteraemia (p<0.001). Embolic events during primary admission were seen more often in the E. faecium group (62.5%) compared to the E. faecalis group (10.7%) (p=0.002). Both groups had multiple co-morbidities without significant differences between groups (Table 1). Nineteen (40.4%) of the patients with E. faecalis IE had a minimum of one previous admission with E. faecalis bacteraemia within the last year before the IE diagnosis, whereas this was not seen for any patients with E. faecium IE. The 30-days all-cause mortality was 5.4% for patients with E. faecalis IE and 25% for patients with E. faecium IE (p=0.22). After a median follow up of 3.1 years (IQR=0.46–3.94) all-cause mortality was 55.4% for patients with E. faecalis IE and 62.5% for patients with E. faecium IE (p=1.00) (Table 1). Conclusion: The prevalence of IE was significantly higher in patients with E. faecalis bacteraemia than with E. faecium bacteraemia. While the prevalence of complications was higher in patients with E. faecium IE, the difference was only significant for embolic events. This indicates that E. faecium IE is associated with a worse outcome compared to the outcome in patients with E. faecalis IE. All-cause mortality was above 50% for both groups, i.e. considerably higher than generally seen in patients with IE. These findings may be of importance of management of patients with E. faecalis or with E. faecium bacteraemia – and endocarditis. Funding Acknowledgement: Type of funding sources: None.